Analisis Rekapitulasi Invoice dan Pelaporan PPh 23 melalui Coretax pada Perusahaan Ekspedisi - Yuseti, Muhammad Ali Fathoni Yuseti; Rahayu, Puji (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the invoice recapitulation process and the reporting of Income Tax Article 23 (PPh Article 23) in an expedition service company through the Coretax system. Expedition service companies are characterized by a high volume of transactions, which requires accurate tax administration, particularly in the withholding and reporting of PPh Article 23. This research employs a descriptive qualitative method with a case study approach. The research data were obtained through document analysis, including service invoices, PPh Article 23 withholding slips, Coretax reporting data, and relevant tax regulations. Data analysis was conducted by examining the conformity between invoice data, withholding slips, and PPh Article 23 reporting in the Coretax system with the applicable tax regulations. The results indicate that the invoice recapitulation and PPh Article 23 reporting processes through Coretax have been implemented systematically; however, potential discrepancies remain in the classification of taxable objects and the accuracy of data input. This study is expected to provide practical contributions for expedition service companies and tax consultants in improving PPh Article 23 administrative compliance, as well as academic insights into the digitalization of tax administration.